Pengembangan Teknologi Ramah Lingkungan Untuk Pengolahan Limbah Padat Menuju Produksi Bebas Limbah - Rina Puji Astutik; Prabandaru Dwi Septian; Indah Nur Andini; Nur Ika Fitriya; Denny Oktavina Radianto (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The development of environmentally friendly technology for processing solid waste towards waste-free production is an important step in maintaining environmental sustainability. Solid waste generated from various sectors has the potential to pollute the environment if not managed properly. The purpose of this article is to discuss the importance of developing environmentally friendly technology in processing solid waste towards waste-free production. The method used in writing this article is using the literature review method. Literature reviews are used to collect information about the types of solid waste produced in Indonesia, technologies that can be used to manage solid waste, as well as the concept of clean production or zero waste production. The development of environmentally friendly technology is the main key in overcoming the solid waste problem, with the potential to create new economic opportunities. To achieve waste-free production, cooperation between government, industry, academia and society is needed. With good cooperation, solid waste management towards waste-free production can become a reality that provides great benefits for the environment, economy and community welfare.